The effect of recombinant vascular endothelial growth factor 121 on nitride oxide level in mice (mus musculus) model of preeclampsia - Soetrisno, Soetrisno; Isharyadi, Isharyadi; Sulistyowati, Sri (Folia Medica Indonesiana, 2017)
Preeclampsia is a multifactorial syndrome in pregnancy whose cause is still unknown. Several proangiogenic and antiangiogenic mediators such as Vascular Endothelial Growth Factor (VEGF) and Nitrite Oxide (NO) play important roles in preventing preeclampsia. VEGF can increase NO level that lowers maternal blood pressure, improves endothelial function and reduces placental hypoxia in preeclampsia. Recombinant VEGF 121 is expected to be an option in the prevention and treatment of preeclampsia. This experimental study used mice (Mus musculus) as the model. The objective of this study was to observe the effect of recombinant VEGF 121 in increasing the level of nitric oxide in mice (Mus musculus) model of preeclampsia. This was an experimental analytical study with Randomized Control Trial (RCT) design. The study enrolled 27 pregnant mice (Mus musculus) which met the restriction criteria divided into 3 groups. The first group (K1) were 9 normal pregnant mice. The second group (K2) were 9 pregnant mice of preeclampsia model without treatment. The third group (K3) were 9 pregnant mice of preeclampsia model receiving recombinant VEGF 121 therapy. The independent variable was the administration of recombinant VEGF 121 and the dependent variable was the serum NO level. Statistical analysis was performed by using anova statistics. NO level in the first group (K1) was 1.746±0.347, with minimum value of 1.00 µM, and maximum value of 2.28 µM, CI (1.479-2.013). NO level in second group (K2) was 1.167±0.380, with minimum value of 0.64 µM, and maximum value of 1.94 µM, CI (0.875-1.460). NO level in the third group (K3) was 2.164±0.556, with minimum value of 1.56 µM, and maximum value of 5.96 µM, CI (1.842-2.486). With anova statistical test, there were significant differences between K1 group and K2 group (p value=0.004<0.05), K1 group and K3 group (p value=0.000<0.05) as well as K2 group and K3 group (p value=0.029<0.05). In conclusion, Recombinant VEGF 121 increased the level of nitric oxide in mice (Mus musculus) model of preeclampsia significantly.